2017
DOI: 10.1016/j.biortech.2017.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent hydrogen production and phosphorus recovery in dual chamber microbial electrolysis cell

Abstract: Concurrent hydrogen (H 2 ) production and phosphorus (P) recovery were investigated in dual chamber microbial electrolysis cells (MECs). The aim of the study was to explore and understand the influence of applied voltage and influent COD concentration on concurrent H 2 production and P recovery in MEC. P was efficiently precipitated at the cathode chamber and the precipitated crystals were verified as struvite, using X-ray diffraction and scanning electron microscopy analysis. The maximum P precipitation effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…9 Struvite has been researched by many authors, but the process has the disadvantage that Mg addition is needed, which makes the process inefficient and expensive. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…9 Struvite has been researched by many authors, but the process has the disadvantage that Mg addition is needed, which makes the process inefficient and expensive. 9,10…”
Section: Introductionmentioning
confidence: 99%
“…Compared with ammonia, P recovery in an MEC is carried out through a different mechanism. Abdullah et al . investigated P recovery in a dual‐chamber MEC, and found that the maximum P precipitation efficiency attained 95% with simultaneous H 2 production.…”
Section: Applications Of the Microbial Electrolysis Cellmentioning
confidence: 99%
“…Furthermore, Cusick and Logan found that the crystal accumulation did not affect the rate of H 2 production in struvite reactors . However, cathode and exchange membrane scaling, as well as pH difference between anode and cathode, can deteriorate MEC performance . To achieve efficient phosphorus recovery, various cathode configurations and electric currents were examined in a lab‐scale MEC experiment for efficient struvite precipitation .…”
Section: Applications Of the Microbial Electrolysis Cellmentioning
confidence: 99%
“…MEC gets noticeable attention as a sustainable wastewater treatment system with energy recovery [33], and many research teams built pilot scale MEC facilities to validate that MEC can be utilized in real industry [34][35][36][37][38][39]. In recent studies, various modified MEC structures are suggested for different applications, such as microbial electrodialysis cell (MEDC) [40], microbial reverse-electrodialysis electrolysis cell (MREC) [41,42], microbial electrolysis struvite-precipitation cell (MESC) [43][44][45], microbial electrolysis desalination and chemical-production cell (MEDCC) [46][47][48][49], and microbial saline-wastewater electrolysis cell (MSC) [50][51][52].…”
Section: Introductionmentioning
confidence: 99%